Answer:
See below ~
Explanation:
Let's get started!
Part (a) :
Statement 1 : ∠A = ∠E = 90° (indicated in diagram)
Statement 2 : ∠C = ∠C (common angle)
⇒ ΔABC ~ ΔBDC (AA similarity)
Part (b) :
Now that we have proved the triangles to be similar, we can take their corresponding sides in proportion.
⇒
![(EC)/(AC) = (ED)/(AB)](https://img.qammunity.org/2023/formulas/mathematics/college/3fh847oa6sh4i46iv40w3k2c8fhyj1oyu5.png)
⇒
![(160)/(160+50) = (120)/(AB)](https://img.qammunity.org/2023/formulas/mathematics/college/l5fm33q1ozdxr7zsrh86s4nyvxogjupsd6.png)
⇒
![(16)/(21) = (120)/(AB)](https://img.qammunity.org/2023/formulas/mathematics/college/kyxmzt84kibgbganfbtvhazx2eg1k2jlqx.png)
⇒
![AB = (120*21)/(16)](https://img.qammunity.org/2023/formulas/mathematics/college/fyzmqse4fkzrd9z86etl4kp0m5b228ohu2.png)
⇒
![AB = (2520)/(16)](https://img.qammunity.org/2023/formulas/mathematics/college/9vqc9mb72rv0q6rh32c7w3phpc5ywue1qx.png)
⇒ AB = 157.5